PERLINDUNGAN HUKUM HAK CIPTA TERHADAP KARYA CIPTA LAGU DAN MUSIK DALAM BENTUK RINGTONE PADA TELEPON SELULER - TOMMY HOTTUA MARBUN; T KEIZERINA DEVI; WINDHA WINDHA (TRANSPARENCY, 2013)
Copyright works in the field of art in the form of song, music, and film is one part of the copyright that should receive legal protection. Copyright, that is, as part of the Law of Intellectual Property has specific characters, namely the appreciation, recognition, legal protectionand has economic value. A song that has been created is essentially intellectual work of a creator,as the embodiment of a sense of quality and the ability of its creator. In this thesis, entitled Protection of Copyright Law Towards Work of Songwriting and Music in the Form of Ringtoneto Cell Phone will discuss how copyright regulation pursuant to Act No.19 of 2002, how Protection of Copyright Law works in the form of songs and music on the ringtone of cell phone,and how disputes over infringement of intellectual songs and music. This study uses normative juridical, that is, a method that examines legislation, legal theories, theories of law and jurisprudence relating to the issues discussed, in this case the approach issued to analyze qualitatively on the Protection of Copyright Law on Songwriting and Music in the Form of Ringtone to Cell Phones. Based on theresults of these studies which conclude that the arrangement of copyright law is regulated in Law Number 19 Year2002 on Copyright, the copyright is subject to exclusive rights to the creator. Legal arrangement is the authenticity protection of creative works and creation, and the rights of the creator.Legal protection of copyrighted songs and music is the legal protection of authenticity (original) of the creation of a personal nature have occurred since the creation of songs and music were born. Settlement of a dispute over the copyright can be conducted either through litigation or non-litigation path. Through Litigation path,theCommercial Courtis filed in accordance with Article 60, and non-litigation path is through Arbitration or Alternative Dispute Resolution(ADR) in accordance with the Article 65 of Law of Copyright.   Kata Kunci :  Hak Cipta, Perlindungan, Ringtone